Mechanics Characteristic Analysis for the Driving Drum Structure of Pipe Belt Convey based on Finite Element Model - Zhang Wenqiang; Bin Guangfu; Li Xuejun; Ye Guilin (Jixie chuandong)
Driving drum as the main driving equipment components of pipe belt conveyor,the traditional empirical formula and bigger safety coefficient method is used to design the structure. In the process of actual operation,the driving drum is influenced by the bending moment and torque coupling effect and dynamic load caused by imbalance. Therefore,the driving drum surface and support bearing are easily damaged. Taking existing same thickness cylindrical,drum type,concave type,three different models drive drum structure as examples,the stress analysis of driving drum is studied,the finite element model is established,the stress distribution and deformation law of the three type structures is obtained and the result is that when the maximum amount of concave is 7% of the diameter,the maximum stress decreased 63% and the maximum deformation decreased 76% comparing with common cylinder. Taking the concave type as an example to analyze dynamic characteristic,critical speed and modal vibration mode are studied. When the unbalance appear in the middle,vibration response and bearing load increases exponentially along with the speed change. The results provide guidance for transmission drum structure design and balance control.